2021
DOI: 10.1093/ajcn/nqaa380
|View full text |Cite
|
Sign up to set email alerts
|

Soft drink consumption and risk of nonalcoholic fatty liver disease: results from the Tianjin Chronic Low-Grade Systemic Inflammation and Health (TCLSIH) cohort study

Abstract: Background Epidemiological evidence for the association of soft drink consumption with nonalcoholic fatty liver disease (NAFLD) is inconsistent, and such association has not been prospectively examined in the general adult population. Objectives We aimed to investigate the prospective association between soft drink consumption and the risk of NAFLD in a Chinese adult population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…In addition, some infrequently consumed foods might have been overlooked due to the limited food items on the FFQ. Although these may influence the accuracy of food intake, it indicated that dietary data were relatively stable over time according to our published studies ( 22 , 50 ). Third, there may be some residual confounding factors we could not fully capture; variables that are intrinsically related to the dietary patterns may influence the relationship between dietary patterns and CA.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, some infrequently consumed foods might have been overlooked due to the limited food items on the FFQ. Although these may influence the accuracy of food intake, it indicated that dietary data were relatively stable over time according to our published studies ( 22 , 50 ). Third, there may be some residual confounding factors we could not fully capture; variables that are intrinsically related to the dietary patterns may influence the relationship between dietary patterns and CA.…”
Section: Discussionmentioning
confidence: 73%
“…The FFQ contained seven frequencies ranging from “almost never” to “twice or more per day” for foods, and eight frequencies ranging from “almost never” to “four or more times per day” for beverages. The reproducibility and validity of the FFQ have been tested in a random sample of 150 participants living in Tianjin by comparing the data from the repeat measure ~3 months apart and 4-day weighed dietary records (WDRs) ( 22 ). Spearman's rank correlation coefficient for energy intake between two FFQs was 0.68, for food items (fruits, vegetables, meat, beverages, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…114 Prospective cohort study supports these findings, by showing a dose-response association between soft drink consumption (mainly sugar-containing carbonated beverages) and NAFLD diagnosed by US; a consumption of 4 or more servings per week was related with 45% increased risk to develop NAFLD. 115 Importantly, high sugar consumption is also related to the risk for liver cancer. 116 This is emphasized explicitly for sugar-sweetened beverages consumption, which is strongly related to the risk of hepatocellular carcinoma (HCC).…”
Section: Core Principles That Need To Be Kept In Any Dietmentioning
confidence: 99%
“…Daily energy and nutrient intakes were extracted from the questionnaires using the China Food Composition database that includes information on nutrient content per gram or serving per product (14) . The reproducibility and validity of the FFQ in measuring food intake have been described in detail previously (24) . The Spearman correlation coefficients between the FFQ and dietary records were 0.49 for energy and 0.68 for organ meats.…”
Section: Assessment Of Dietary Intakementioning
confidence: 99%